Melatonin influence on miRNA expression in sperm, hypothalamus, pre-frontal cortex and cerebellum of Wistar rats. - Mísia Helena da Silva Ferro; Ingrid Morante; Fernanda Akane Nishino; Camila Estevam; Fernanda Gaspar do Amaral; José Cipolla-Neto; Taiza Stumpp (PLoS ONE)
Melatonin is a pineal hormone synthesized exclusively at night, in several organisms. Its action on sperm is of particular interest, since they transfer genetic and epigenetic information to the offspring, including microRNAs, configuring a mechanism of paternal epigenetic inheritance. MicroRNAs are known to participate in a wide variety of mechanisms in basically all cells and tissues, including the brain and the sperm cells, which are known, respectively, to present 70% of all identified microRNAs and to transfer these molecules to the embryo. MicroRNAs from sperm have been associated with modulation of embryonic development and inheritance of psychiatric symptoms, including autism. Given that microRNAs and melatonin are ubiquitous molecules with important roles in the organism, the aim of this study was to investigate the expression of specific microRNAs in sperm, brain and cerebellum of pinealectomized rats. For this study, Wistar rats had their pineal gland removed at 60 post-partum. Part of these rats received exogenous melatonin until the day of the euthanasia. The control group did not receive any treatment or manipulation. The sperm, hypothalamus, prefrontal cortex and cerebellum were collected for analysis of microRNA expression by RT-qPCR. The results suggest that melatonin absence caused by pinealectomy increases the expression of the target microRNAs in the sperm. Although the data suggest an alteration (increase or decrease depending on the region and microRNA) of expression levels of some microRNAs in the brain and cerebellum of pinealectomized rats, the differences were not statistically significant. This seems to be a consequence of the intragroup variation. Melatonin administration restored the levels of the target microRNAs in the sperm. Additional studies are needed to understand the impact of the alterations of microRNA expression to the pinealectomized rats as well as to their descendants.